2010
DOI: 10.1371/journal.pone.0009504
|View full text |Cite|
|
Sign up to set email alerts
|

A Crucial Role for Kupffer Cell-Derived Galectin-9 in Regulation of T Cell Immunity in Hepatitis C Infection

Abstract: Approximately 200 million people throughout the world are infected with hepatitis C virus (HCV). One of the most striking features of HCV infection is its high propensity to establish persistence (∼70–80%) and progressive liver injury. Galectins are evolutionarily conserved glycan-binding proteins with diverse roles in innate and adaptive immune responses. Here, we demonstrate that galectin-9, the natural ligand for the T cell immunoglobulin domain and mucin domain protein 3 (Tim-3), circulates at very high le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
192
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 170 publications
(203 citation statements)
references
References 51 publications
9
192
2
Order By: Relevance
“…We also saw enhanced spontaneous apoptosis of Tim-3-expressing cells after cytokine induction, even without the addition of galectin-9. One potential explanation for this observation is galectin-9 upregulation on stimulated cells in culture, because galectin-9 is upregulated on multiple cell types during immune activation via IFN-g and IL-1b (34)(35)(36)(37). Thus, although IL-2 and IL-15 are generally considered to be prosurvival for T cells, they can also have indirect, proapoptotic effects through the upregulation of Tim-3 and possibly galectin-9.…”
Section: Discussionmentioning
confidence: 99%
“…We also saw enhanced spontaneous apoptosis of Tim-3-expressing cells after cytokine induction, even without the addition of galectin-9. One potential explanation for this observation is galectin-9 upregulation on stimulated cells in culture, because galectin-9 is upregulated on multiple cell types during immune activation via IFN-g and IL-1b (34)(35)(36)(37). Thus, although IL-2 and IL-15 are generally considered to be prosurvival for T cells, they can also have indirect, proapoptotic effects through the upregulation of Tim-3 and possibly galectin-9.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Gal-9 is expressed by eosinophils, endothelial cells, T lymphocytes, DCs, macrophages, lymphoid cells, Kupffer cells, intestinal epithelial cells, and vascular endothelial cells. 10,[14][15][16][17][18][19] Wide distribution of Gal-9 on host cells demonstrates an important but complex role for this lectin, whose biologic effects are exerted by 2 receptors with distinct, and often opposing effects: TIM-3 (T-cell immunoglobulin [Ig] and mucin domain-containing molecule 3) 20 and cell surface protein disulfide isomerase (PDI). 21 Tim-3 negatively regulates Th1 responses on interaction with Gal-9.…”
Section: Introductionmentioning
confidence: 99%
“…This low-response state to PAMPs in KCs is called endotoxin tolerance, and is caused by negative regulation of the TLR signaling pathway, soluble immune regulatory molecules or even epigenetic modification. 34 A higher level of IL-10 mRNA expression was detected in monocytes from chronic HCV patients. 35 Studies have shown that HCV core protein induces KCs to secrete IL-10, in order to suppress secretion of pro-inflammatory factors.…”
Section: Il-10 and Tgf-βmentioning
confidence: 95%